Comparative analysis of swine leukocyte antigen gene diversity in Göttingen Minipigs - Sabine E. Hammer; Tereza Duckova; Monica Gociman; Sandra Groiss; Clara P. S. Pernold; Karolin Hacker; Lena Kasper; Julia Sprung; Maria Stadler; Andres Eskjær Jensen; Armin Saalmüller; Nadine Wenzel; et al. (Frontiers in Immunology, 2024)
Worldwide, pigs represent economically important farm animals, also representing a preferred preclinical large animal model for biomedical studies. The need for swine leukocyte antigen (SLA) typing is increasing with the expanded use of pigs in translational research, infection studies, and for veterinary vaccine design. Göttingen Minipigs (GMP) attract increasing attention as valuable model for pharmacological studies and transplantation research. This study represents a first-time assessment of the SLA gene diversity in Göttingen Minipigs in combination with a comparative metadata analysis with commercial pig lines. As Göttingen Minipigs could harbor private as well as potential novel SLA allele combinations, future research projects would benefit from the characterization of their SLA background. In 209 Göttingen Minipigs, SLA class I (SLA-1, SLA-2, SLA-3) and class II (DRB1, DQB1, DQA) genes were characterized by PCR-based low-resolution (Lr) haplotyping. Criteria and nomenclature used for SLA haplotyping were proposed by the ISAG/IUIS-VIC SLA Nomenclature Committee. Haplotypes were assigned based on the comparison with already known breed or farm-specific allele group combinations. In total, 14 SLA class I and five SLA class II haplotypes were identified in the studied cohort, to manifest in 26 SLA class I but only seven SLA class II genotypes. The most common SLA class I haplotypes Lr-24.0 (SLA-1*15XX or Blank-SLA-3*04:04-SLA-2*06:01~02) and Lr-GMP-3.0 (SLA-1*16:02-SLA-3*03:04-SLA-2*17:01) occurred at frequencies of 23.44 and 18.66%, respectively. For SLA class II, the most prevalent haplotypes Lr-0.21 (DRB1*01XX-DQB1*05XX-DQA*04XX) and Lr-0.03 (DRB1*03:02-DQB1*03:01-DQA*01XX) occurred at frequencies of 38.28 and 30.38%. The comparative metadata analysis revealed that Göttingen Minipigs only share six SLA class I and two SLA class II haplotypes with commercial pig lines. More importantly, despite the limited number of SLA class I haplotypes, the high genotype diversity being observed necessitates pre-experimental SLA background assessment of Göttingen Minipigs in regenerative medicine, allo-transplantation, and xenograft research.